Combined effect of conventional antimicrobials with essential oils and their main components against resistant Streptococcus suis strains (2019)
Streptococcus suis is a major swine pathogen. Different strategies to reduce the antimicrobial resistance to conventional antimicrobials (AMBs) have been proposed, including the combined use with essential oils (EOs). The objective of this work was to evaluate the effectiveness of the combination of cinnamon, oregano, common thyme and red thyme EOs and their main components (cinnamaldehyde, carvacrol and thymol) with conventional AMBs (oxytetracycline, trimethoprim-sulfamethoxazole, gentamicin and penicillin) against field resistant S. suis strains. The checkerboard method was used to assess the interaction, by the fractional inhibitory concentration index (FIC index ) determination. All the AMBs showed synergistic (FIC index  = 0·5) or additive (0·5 < FIC index  = 1) effect with at least one of the four essential oils. In general, the combination of the AMBs with the EOs showed better results than combination the AMBs with the main components, although no antagonist effects were detected in any case. The results obtained would support the combined use of AMBs agents with EOs for the treatment of S. suis. Significance and Impact of the Study: Streptococcus suis is an important pig pathogen and a zoonosis. Control is based on antimicrobials; however, there is pressure to reduce the use of antimicrobials and new products or combination therapies are of considerable interest. We have evaluated the combined interaction of four essential oils or their main components with conventional antimicrobials against resistant S. suis strains. A positive interaction between gentamicin and oxytetracycline with cinnamon, oregano or thyme was observed, suggesting that a combination of conventional antimicrobials with EOs is a promising alternative for the control of S. suis infections. © 2019 The Society for Applied Microbiology